The Role of Correction Guardians In The Development of Private In Class I Surabaya Criminal Institutions - Agung Wibowo Darmawan; Priambodo Adi Wibowo; Asep Heri (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
Sanctions for criminal acts committed. The role of correctional guardians is needed in the process of fostering Correctional Families who are the target of coaching carried out in Correctional Institutions. This research is a qualitative research with a descriptive approach that aims to describe the role of correctional guardians in fostering correctional inmates in Class I Lapas Surabaya. Data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques begin with data collection, data reduction, data triangulation, data presentation and drawing conclusions and verification. The results of this study indicate that the coaching process at Class I Lapas Surabaya is running effectively according to the goals of correctional through the role of correctional guardians as facilitators, communicators, and motivators. Efforts that need to be maximized in coaching require psychologists or special social workers as correctional guardians.